2017
DOI: 10.1093/geront/gnw165
|View full text |Cite
|
Sign up to set email alerts
|

Adult Day Center Programs and Their Associated Outcomes on Clients, Caregivers, and the Health System: A Scoping Review

Abstract: As the population ages, policymakers must carefully consider how ADCs can best serve each user and their caregivers with their unique circumstances. ADCs have the potential to help shape health system interventions, especially those targeting caregivers and people requiring long-term care support. Due to the variation among types of ADC programs, future research on ADCs should consider different characteristics of ADC programs to better contextualize their results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 29 publications
2
52
0
1
Order By: Relevance
“…4 These services should also serve as a respite for family caregivers, and it is claimed that such services may delay nursing home placement. 4 , 7 9 A recent Norwegian study found higher self-reported quality of life among people with dementia attending day care services compared to those not receiving day care. 10 By 2020, all Norwegian municipalities will be obliged to offer day care to people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…4 These services should also serve as a respite for family caregivers, and it is claimed that such services may delay nursing home placement. 4 , 7 9 A recent Norwegian study found higher self-reported quality of life among people with dementia attending day care services compared to those not receiving day care. 10 By 2020, all Norwegian municipalities will be obliged to offer day care to people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research [19,26,27], DCCs show a positive effect on the well-being of older adults who visit DCCs regularly. To date, mainly clinical effectiveness of non-pharmacological treatments for community-dwelling people with cognitive impairments and their caregivers was assessed (e.g., [14,16,19,25,27,28]).…”
Section: Introductionmentioning
confidence: 92%
“…The prerequisites for receiving day care depend on the individual's need and the availability of a caregiver during day [22,23]. Independent from financing day care, similar models as above described "care as usual" day care exist in other industrialized countries [19,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on Adult Day Programs (ADP) catering to older adults with impairments related to aging, is much more extensive 19 than the literature about MSADPs; however, findings on participant satisfaction and health outcomes are similar to those for MSADPs. Scholarly reviews suggest that participants generally are satisfied with services, 19,20 and that programs increase participants' emotional well-being, 20 but evidence of improvement in health or ADLs is lacking.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%